2013
DOI: 10.11646/zootaxa.3737.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Tylototriton from Thailand (Amphibia: Urodela: Salamandridae)

Abstract: Three morphological groups are found in a salamandrid newt Tylototriton shanjing from Thailand. We describe two of them as new species, one from northern and the other from northeastern Thailand, based on molecular and morphological data, however we could not make a taxonomic decision on the remaining one group because of the lack of voucher specimens and sufficient genetic data. The northern species differs morphologically from all known congeners by having the combination of orange to reddish brown markings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 20 publications
5
42
0
Order By: Relevance
“…Samples from Luang Phabang, Xieng Khouang and Huaphanh Provinces formed a unique clade within an unresolved polytomy containing T. verrucosus, T. shanjing, and T. v. pulcherrima from China and Myanmar. This fourth Laos clade has an unclarified identity, and matched published Huaphanh Province sequences referred to as T. shanjing or T. v. verrucosus (Nishikawa et al 2013a;Le et al 2015). Sequences of this fourth Laos clade had uncorrected pairwise distances of 2.1-4.6% from other lineages of T. shanjing and T. verrucosus from China and Myanmar (Table 2).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Samples from Luang Phabang, Xieng Khouang and Huaphanh Provinces formed a unique clade within an unresolved polytomy containing T. verrucosus, T. shanjing, and T. v. pulcherrima from China and Myanmar. This fourth Laos clade has an unclarified identity, and matched published Huaphanh Province sequences referred to as T. shanjing or T. v. verrucosus (Nishikawa et al 2013a;Le et al 2015). Sequences of this fourth Laos clade had uncorrected pairwise distances of 2.1-4.6% from other lineages of T. shanjing and T. verrucosus from China and Myanmar (Table 2).…”
Section: Resultssupporting
confidence: 60%
“…The genus was only recently documented in the country with the description of T. notialis Stuart, Phimmachak, Sivongxay & Robichaud 2010 from Khammouan Province, central Laos. Additional records of the genus from the country (as T. verrucosus verrucosus or T. shanjing) have been cited only as voucher specimens (Matsui 2013;Nishikawa et al 2013a;Le et al 2015), or shown in photographs (Sparreboom 2014), with no descriptive information.…”
Section: Introductionmentioning
confidence: 99%
“…; Carranza and Wade ; Nishikawa et al. ). Nevertheless, colour polymorphism seems to occur in populations of Salamandra salamandra (Linnaeus ), a member of the Salamandridae, although only anecdotal descriptions are available concerning the presence of this phenomenon (Eiselt ; Malkmus ; Barrio and Fonoll ; Pasmans and Keller ).…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of newt diversity in the region has changed dramatically in recent years, with the number of species recognised from the region increasing threefold since 2000 (Frost, 2016). This is a result of increased survey effort and the incorporation of molecular data in resolving species boundaries in the morphologically conserved taxa (Le et al, 2015;Nishikawa et al 2013Nishikawa et al , 2014Phimmachak et al, 2015a;Stuart et al 2010). Undescribed diversity likely remains (Nishikawa et al, 2013, Sparreboom, 2014 and the basic biology, ecology and true conservation status of known Southeast Asian newts remains poorly-known (Phimmachak et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Of the nine assessed species, five are considered threatened with extinction, and three are near threatened (Table 1). Tylototriton verrucosus is the only species of newt in Southeast Asia that is currently considered Least Concern, but since the assessment was performed (van Dijk et al, 2009), new research has shown that this species actually consists of a a complex of several species, each having narrower ranges and thus more likely to be threatened (e.g., Nishikawa et al, 2013Nishikawa et al, , 2014Phimmachak et al, 2015a;Le et al, 2015;). For example, one recently described species previously thought to be T. verrucosus, T. shanorum, is endemic to Myanmar (Nishikawa et al, 2014), where it is currently known only from a few ponds at risk of development (G. Wogan, pers.…”
Section: Introductionmentioning
confidence: 99%